DEVELOPMENT AND VALIDATION OF THE QUESTIONNAIRE "PECULIARITIES OF SEXUALITY OF PEOPLE 60+" - Marina SLAVINSKI; Svetlana TOLSTAIA (Universitaria Publishing House, Craiova, 2023)
The article describes the procedure for the development and validation of the author's questionnaire "Features of the sexuality in adults 60+". It presents the results of methodological testing of a cohort of Russian-speaking Israeli adults 60 to 91 years old. To our knowledge, the proposed survey is the first psychometric tool that allows diagnosing the characteristics of the sexuality of older people such as "stereotypes about sexuality", "sexual behavior", "sexual health", "attitude towards the body", and also allows measuring the overall level of sexuality. Unlike previous clinical and sexology scales, this tool is not aimed at identifying problems in the sexual space of the elderly, but at identifying the specific features and characteristics of the sexuality of older adults. Studies that used this questionnaire indicate sufficient construct validity and high reliability for internal consistency (Cronbach's Alpha of 0.943). The content validity of the survey was confirmed using the expert review methodology, with Spearman's correlation coefficient between the first and second examinations of 0.975, which indicates the stability of the survey's outcomes. The collected data suggested that the proposed questionnaire is a reliable diagnostic tool for both research purposes and for practical use by clinicians working with older adults (e.g.., psychologists, sexologists, social workers).